Inventory Reduction and Productivity Growth: Linkages in the Japanese Automotive Industry - Lieberman, Marvin B.; Demeester, Lieven (Management Science, 1999)
The literature on JIT production suggests a causal link between work-in-process inventory and manufacturing productivity. Such a connection has been described in numerous case studies but never tested statistically. This paper uses historical data for 52 Japanese automotive companies to evaluate the inventory-productivity relationship. We find that firms increased their productivity rank during periods of substantial inventory reduction. More detailed tests suggest that inventory reductions stimulated gains in productivity: On average, each 10% reduction in inventory led to about a 1% gain in labor productivity, with a lag of about one year. Such effects were more immediate for Toyota affiliates, but undetectable for close suppliers of Nissan. These findings imply that inventory reduction served as an important driver of process improvement for many Japanese automotive companies, although some firms emphasized other methods.